Engineered Sleeping Beauty transposase redirects transposon integration away from genes. Issue 5 (21st February 2022) - Miskey, Csaba; Kesselring, Lisa; Querques, Irma; Abrusán, György; Barabas, Orsolya; Ivics, Zoltán
Abstract: The Sleeping Beauty (SB) transposon system is a popular tool for genome engineering, but random integration into the genome carries a certain genotoxic risk in therapeutic applications. Here we investigate the role of amino acids H187, P247 and K248 in target site selection of the SB transposase. Structural modeling implicates these three amino acids located in positions analogous to amino acids with established functions in target site selection in retroviral integrases and transposases. Saturation mutagenesis of these residues in the SB transposase yielded variants with altered target site selection properties. Transposon integration profiling of several mutants reveals increased specificity of integrations into palindromic AT repeat target sequences in genomic regions characterized by high DNA bendability. The H187V and K248R mutants redirect integrations away from exons, transcriptional regulatory elements and nucleosomal DNA in the human genome, suggesting enhanced safety and thus utility of these SB variants in gene therapy applications.